A Study Of Translation Based Meaning Variations as Reflected in John Steinbeck’s Of Mice and Men and Pramoedya Ananta Toer’s Tikus dan Manusia - Chusna Apriyanti (LPPM Press, 2015)
The objectives of this research were to find out the meaning variations between JohnSteinbeck’s of Mice and Men (original version) and Premoedya Ananta Toer’s Tikusdan Manusia (translated version) and the probable reasons that motivate the occurrenceof meaning variations between John Steinbeck’s of Mice and Men (original version)and Premoedya Ananta Toer’s Tikus dan Manusia (translated version). This researchwas descriptive quantitative research. The data were gathered through reading both ofthe novels and putting the clauses into the table to be analyzed. The results showedthat the meaning differences between SL and TL were classified into seven levels ofmeaning differences: the lowest differences, very low differences, low differences,medium differences, high differences, very high differences, and the highest differences.The meaning differences were caused by eleven factors, namely the element and clauseomission, the element and clause addition, the changing of word, the different sense ofword, the use of informal word in SL and the formal word in TL, the deletion of markingrelationship/conjunction between clauses, the use of idioms, the use of active formationin SL and passive formation in TL, the changing of back and forth formation or structureshift.